E-Raser: File Shredder Application With Content Replacement by Using Random Words Function - Nur Farah Aqilah Mohd Nahar; Nurul Hidayah Ab Rahman; Kamarudin Malik Mohammad (JOIV : International Journal on Informatics Visualization, 2018)
Data shredding indicates a process of irreversible file destruction while file shredder is the program designed to render computer-based files unreadable by implementing overwriting method to destroy data in the content of a file. The addressable problem with existence of file recovery tools is it may lead to data leakage, exploitation or dissemination from an unauthorized person. Thus, this study proposed a file shredding application named E-Raser which replacing the content of the file using random words function algorithm. A file shredder application named E-Raser was developed to shred Microsoft Word documents with (.doc) or (.docx) format. The implemented algorithm replaced the original content of the files with uninformative words provided by the application. After rewriting phase is complete, shredding process take place to make the file unrecoverable. Object Oriented Software Development was used as the methodology to develop this application. As a result, E-Raser achieved the objectives to add, remove, rewrite, display and shred files. Also, E-Raser is significantly facilitates users to securely dispose their file, protect the confidentiality and privacy of the file’s content.